PERANCANGAN ALAT PENCAMPUR PASIR CETAK âTURBO MIXERâ - Budiwantoro, Bagus; Adikara, Bayu Pratama (Mesin, 1998)
Turbo Mixer with 350 kg capacity is designed to mix greensand by mixing it using turbo blade rotation so it creates a mix using scatter method. Using this method, the greensand will not be damaged during the process. The turbo blade rotation with lateral mixing arm was set in a way that the mixer could work efficiently. The construction of this turbo mixer is rigid but simple to ensure the easiness of operating, maintenance and manufacturing. In other application, Turbo Mixer could be developed for mixing of fertilizers, drugs etc. Several design practice ï¬gures for 350 kg turbo mixer, are taken from the recalculation of 750 kg turbo mixer that have been made before.